Semiotics of Clothing in the Novel Tawq Al-Hamam: A Reading of Cultural and Social Symbols - Khomayyies, Arwa Dawood (Journal of Humanities & Social Sciences, 2025)
This research examines the semiotics of clothing in the novel Tawq Al-Hamam by Raja Alem, through an analysis of the cultural symbols and social meanings associated with dress as a tool for conveying layered societal and historical dimensions. The study aims to uncover how garments are employed to shape the literary identity of characters and to highlight class and social distinctions through visual elements embedded in clothing.The research adopts a semiotic methodology rooted in the theories of Roland Barthes and Yuri Lotman, focusing on the reading of cultural signs within literary texts. Due to the scarcity of visual or documented references to popular dress in Mecca prior to the establishment of the Saudi state, the study relies on the novel’s narrative memory as a storytelling archive that expresses the lived realities of society and illuminates the specificity of time and place.The findings reveal that clothing in the novel is not merely descriptive, but serves as a profound semiotic device—subtly documenting popular history and collective memory through fabric, silhouettes, and stylistic expression. The study concludes that clothing plays an active role in constructing the psychological depth of characters and mirrors the social transformations in Hijaz during the final phase of Ottoman rule.This study recommends further exploration of clothing as a cultural text within literature and highlights the potential of this lens to inform creative domains such as theatre, screen production, and children’s literature—reviving collective memory through visual and imaginative narratives.
Keywords: Semiotics of Fashion; Tawq Al-Hamam; Cultural Symbols; Meccan Identity; Collective Memory